Motivation of elementary school students in learning of physical education, sport and healt during pandemic - Ardonansyah, Muhamad; Hardiyono, Bayu; Hidayat, Arif (Journal Coaching Education Sports, 2021)
This study aims to determine the motivation of elementary school students in learning physical education, sports and health during the pandemic. The population in this study was 15 elementary schools in Ilir Timur I Subdistrict, Palembang The results of the study on student motivation show that 100% of teachers continue to provide learning motivation to students during the pandemic and of teachers provide answers by giving healthy greetings and enthusiasm to students during the pandemic. The PJOK learning process showed that 100% of teachers collaborated with parents so that PJOK learning was carried out well during the pandemic and provided tutorials through videos and powerpoints for students to learn PJOK learning during the pandemic. Learning constraints show 93,3% of teachers have not mastered the use of online media in implementing corner learning during the pandemic, of teachers have difficulty accessing the internet in carrying out PJOK learning during the pandemic and of teachers provide other answers in the form of not being able to practice directly, teaching aids are lacking adequate, difficult for children who do not have cellphones or do not have quotas to study, there are no difficulties, it is difficult to communicate with students who do not have cellphones. It is hoped that in the future sports teachers will continue to provide motivation and varied PJOK learning during the pandemic.